PENGARUH LATIHAN WALKING LUNGES TERHADAP TENDANGAN MAWASHI GERI PADA CABANG OLAHRAGA KARATE PADA ANAK USIA 11-14 TAHUN DI DOJO ASPOL KPPP BENOWO SURABAYA - EKA HUTANTY, PUTRIE Eka (Jurnal Prestasi Olahraga, 2013)
Science and technology in Indonesia, especially Sports , has been an important thing to be improved by scholars and group of experts who are competent in thus field One thing that should be considered is about martial art especially karate. Karate in Indonesia still uses conventional practicing method, therefore it an needs optimal attempt to improve, it since karate is very potential to get great achievement. This research is aimed to investigate the effect of walking lunges practice on mawashi geri kick within 28 seconds. It is because the frequency of practice especially in Dojo (a place for practicing Karate) in Surabaya tends to use hitting (Gyaku). In fact, Gyaku has less point than Mawashi geri kick. This problem should be changed by the portion of practicing in order to make the athletes accustomed to perform their kicking that hitting in the real kumite.The type of this research was quantitative research with One-Group Pretest-Postest Design approach. The subjects of this research were early age athletes between 11 to 14 years old. In addition, to analyze the data in this research, the researcher used manual analyzing technique.From the manual data analysis, it can be seen that there were some increases as follows : there was 5.14% increase on front right mawashi geri kick, 3.94% increase on front left mawashi geri kick, 3.44% increase on back right mawashi geri kick, 8.82% increase on back left mawashi geri kick. On the other hand, there was not much increase on back right mawashi geri kick because the tvalue = 3 > 3.182 ttable with 0.05 significant, df = 3. Therefore, to conclude, the increase was 4.98%Keywords : Walking Lunges as Alternative Kick Practicing